About the disregard of legal entity doctrine in Brazilian anti-corruption act (Law no. 12,846/2013) - José Sérgio da Silva Cristóvam; Gustavo Costa Ferreira (Revista de Direito Econômico e Socioambiental)
The purpose of this review is to analyze the disregard of the legal entity provision in the Brazilian Anti-Corruption Law (Law no. 12,846/13), intended to sanction juristic persons for harmful acts against the Public Administration. It aims to establish criteria for the interpretation and application of the disregard provision in study. In order to do so, we reviewed the birth context of the aforementioned federal law, we studied the constitutionalization of law phenomenon and its contribution to the structuring of a Punitive Administrative legal regime. Therefore, essentials concepts and premises to this investigation were established in light of the Punitive Administrative Law. Then, a necessary introduction was made to the disregard of legal person technique in Brazilian legislation. Finally, we suggested criteria for the interpretation and application of article 14, of the Law 12,846/13.